Patients with HIV and cirrhosis: the risk for hepatocellular carcinoma after direct-acting antivirals for hepatitis C virus. (1st October 2021) - Guardigni, Viola; Toschi, Alice; Badia, Lorenzo; Rosselli Del Turco, Elena; Salsi, Eleonora; Cristini, Francesco; Sighinolfi, Laura; Fabbri, Gabriele; Massari, Marco; Cuomo, Gianluca; Viale, Pierluigi; Verucchi, Gabriella
Abstract : Objectives: Hepatocellular carcinoma (HCC) has become a major issue in coinfected HIV/HCV patients with liver cirrhosis. We aimed to determine the rate of HCC occurrence after a direct-acting antiviral (DAA) treatment and to evaluate the factors associated with the risk of HCC in this population. Design: We conducted a retrospective multicenter observational study including cirrhotic HIV/HCV-coinfected patients treated with DAAs, between October 2014 and January 2017. Methods: We collected demographics characteristics, data regarding HIV and HCV infections and treatment with DAAs. We investigated the rate and the time of occurrence of HCC. Statistical analysis explored the factors associated to development of liver cancer. Results: During a median follow-up of 55 months, 24 out of 232 patients developed HCC, after a median of 22.5 months from starting DAAs. Factors associated with HCC were a higher Child–Pugh Turcotte (CPT) score ( P = 0.002), HCV genotype 3 ( P = 0.04), previous HCC ( P < 0.001) and CD4 + cell count nadir greater than 350 cells/μl ( P = 0.001), whereas antiretroviral therapy (ART) was associated to a lower rate of cancer ( P = 0.02). At multivariable analysis CPT score and a history of HCC remained independently associated with HCC after DAAs ( P = 0.003 and P < 0.001, respectively), and ART administration maintained its protective role ( P = 0.047), regardless of HIV RNA at baseline. Conclusion: Our study highlights the importance of a long-lasting follow-up for HCC after HCV eradication, mostly in those patients with advanced cirrhosis and history of HCC. Furthermore, our data showed a potential role of ART itself (and not of undetectable HIV RNA) in reducing the risk for HCC development. Abstract : Supplemental Digital Content is available in the text